1999
DOI: 10.1136/hrt.82.6.726
|View full text |Cite
|
Sign up to set email alerts
|

External cardioversion of atrial fibrillation: role of paddle position on technical efficacy and energy requirements

Abstract: Aim-To define the eVect of defibrillator paddle position on technical success and dc shock energy requirements of external cardioversion of atrial fibrillation. Methods-301 patients (mean (SD) age 62 (11) years) with stable atrial fibrillation were randomly assigned to elective external cardioversion using anterolateral paddle position (ventricular apex-right infraclavicular area; group AL (151 patients)) or anteroposterior paddle position (sternal body-angle of the left scapula; group AP (150 patients)). A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
3
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 26 publications
2
79
3
9
Order By: Relevance
“…3,9,15) In contrast, our data revealed that even in patients with relatively long AF duration, eg, > 6 months (median 9 months), success rates were similar to those in patients of AF duration < 6 months. Therefore, our data suggest that DC treatment administered to control AF rhythm should not be overlooked when treating patients with prolonged AF duration.…”
Section: )contrasting
confidence: 51%
See 3 more Smart Citations
“…3,9,15) In contrast, our data revealed that even in patients with relatively long AF duration, eg, > 6 months (median 9 months), success rates were similar to those in patients of AF duration < 6 months. Therefore, our data suggest that DC treatment administered to control AF rhythm should not be overlooked when treating patients with prolonged AF duration.…”
Section: )contrasting
confidence: 51%
“…Several studies suggest a higher cardioversion success rate when pads are positioned over the right parasternal area or sternal body and the left infrascapular area, rather than when electrode pads are conventionally positioned. [7][8][9][10] However, the differences in cardioversion success rate due to differing pad positions have not been confirmed by other studies. 5,6,11) Recently, a small, nonrandomized, and nonprospective study by Mehdiard, et al 11) suggested that improved DC cardioversion efficacy in patients with AF could be achieved by positioning pads under fluoroscopy to encompass as much atrial muscle as possible.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Twenty-two studies have compared specific cardioversion strategies (eg, monophasic versus biphasic defibrillators and different energy levels) administered by cardiologists in the hospital setting to patients with atrial fibrillation (both acute and chronic) (LOE 1 14,17,26,27,31,[102][103][104][105][106][107][108][109][110][111][112][113][114][115] ; LOE 2 116,117 ). Most of these studies documented that biphasic shocks were more effective than monophasic shocks for cardioversion.…”
Section: Consensus On Sciencementioning
confidence: 99%